1996
DOI: 10.1111/j.2042-7158.1996.tb05974.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Excretion and Accumulation Kinetics of 2-Methylbenzoylglycine in the Isolated Perfused Rat Kidney

Abstract: The effect of protein binding on kidney function has been studied by investigating the renal accumulation and secretion of the hippurate analogue 2-methylbenzoylglycine in the isolated perfused rat kidney in the absence and presence of bovine serum albumin (BSA), Experiments were performed with either 2-5% pluronic or a combination of 2-2% pluronic and 2% BSA as oncotic agents; a wide concentration range (1-190 fig inL~1) of 2-methylbenzoylglycine was studied. Tubular secretion appeared to be a function of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…In the current study 4-methylbenzoylglycine did not affect mitochondrial oxygen consumption, which is a good indication that the compound does not interfere with mitochondrial metabolism. 2-Methylbenzoylglycine affected mitochondrial oxygen consumption slightly, but not significantly, which is in agreement with its moderate effect on kidney function (Masereeuw et al 1996a). p-Aminohippurate, however, significantly inhibited both state 2 and state 3 of succinatestimulated respiration.…”
Section: Compoundsupporting
confidence: 73%
“…In the current study 4-methylbenzoylglycine did not affect mitochondrial oxygen consumption, which is a good indication that the compound does not interfere with mitochondrial metabolism. 2-Methylbenzoylglycine affected mitochondrial oxygen consumption slightly, but not significantly, which is in agreement with its moderate effect on kidney function (Masereeuw et al 1996a). p-Aminohippurate, however, significantly inhibited both state 2 and state 3 of succinatestimulated respiration.…”
Section: Compoundsupporting
confidence: 73%
“…Since MRP4 and BCRP are located at the apical membrane of proximal tubule cells, transport activity depends on the intracellular levels of substrates rather than substrate concentrations in the blood. Previously, Masereeuw et al demonstrated that methyl hippuric acids accumulate during secretory transport in the isolated perfused rat kidney [20], [21]. Furthermore, they showed that 2-methyl hippuric acid levels were 175-times higher in kidney tissue compared to the perfusate and 4-methyl hippuric acid concentrations were even 600-times higher.…”
Section: Discussionmentioning
confidence: 97%
“…where C1R = renal clearance (ml/min); R r = renal excretion rate (pg/min); Qgf = glomerular filtration rate (ml/min); Cp = drug concentration in perfusate (pg/ml); Tm = maximum tubular transport velocity (pg/min); Kr = Michaelis-Menten constant of secretion (pg/ml): and FPr = fraction of excreted drug reab sorbed passively [14,15].…”
Section: Renal Excretion Modelmentioning
confidence: 99%
“…where Rm = maximum capacity of renal accumulation (pg/g); Ka = affinity constant of renal accumulation (pg/ml); and a = ratio CT/CP due to passive transport [15].…”
Section: Accumulation In Kidney Tissuementioning
confidence: 99%